(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
This study examines diseases that affected the livestock sector in Malaya from 1895 to 1930. The contagious diseases—rinderpest and foot and mouth disease (FMD)— significantly jeopardised the livestock economy. They were detected in imported cattle and buffaloes from India and Siam (Thailand), entering through ports such as Port Weld, Port Swettenham, and Port Dickson. The spread of these diseases led to the establishment of the veterinary branch within the medical department, which remained active until early 1930. Using a qualitative approach, this article draws on sources from the National Archives of Malaysia, the Internet archives and the Tun Seri Lanang Library (Universiti Kebangsaan Malaysia), including Colonial Office files (CO 576), official letters, medical reports and Federated Malay States administrative reports. The research identifies rinderpest as the primary cause of livestock deaths, particularly among buffaloes. Effective prevention measures included quarantining imported cattle at quarantine stations and using anti-rinderpest serum from India.